Exploring Reading Comprehension Problems Encountered by EFL Students - Ulandiari, Kadek Semi (Jurnal Ilmu Multidisiplin Indonesia, 2024)
AbstractThis qualitative research aims to explore the reading comprehension problems encountered by eleventh grade students at SMK TI Bali Global Singaraja in academic year 2023/2024 and the solutions that students do when experience reading comprehension problems in English reading. Data were collected through observation methods, semi-structured interviews, and documentation involving a purposive sample of eleventh grade students. The results of this study indicate that the reading comprehension difficulties faced by eleventh grade students of SMK TI Bali Global Singaraja are as many as 33.33% of students have difficulty in determining the main idea (3 students), 33.33% of students have difficulty in finding references (3 students), 100% of students have difficulty in understanding new vocabulary (9 students), 55.56% of students have difficulty in making conclusions (6 students), and 22.22% of students have difficulty in finding detailed information in English reading (2 students). And when students experiencing problems understanding English reading comprehension, there are several solutions that are usually carried out by eleventh grade students at SMK TI Bali Global Singraja, such as asking (asking for help) to the teacher, asking for help from friends who understand better, Rereading (repeatedly), Matching and adjusting it to the reading concept, Translating the texts first (use Google Translate or a dictionary). The findings of this study contribute to a deeper understanding of the reading comprehension challenges faced by Indonesian vocational high school students and inform the development of effective pedagogical approaches to improve their reading skills.